Factors Associated with Change in Adherence to Covid-19 Personal Protection Measures in the Metropolitan Region, Chile - Vargas-Rona, C; Elorrieta-Lopez, F; Maddaleno-Herrera, M; Villalobos-Dintrans, P; Castillo-Corral, C; Ayala, A (Public Library of Science, 2022)
Personal protective measures such use of face masks, hand washing and physical distancing have proven to be effective in controlling the spread of the Covid-19 pandemic. However, adherence to these measures may have been relaxed over time. The objective of this work is to assess the change in adherence to these measures and to find factors that explain the change For this purpose, we conducted a survey in the Metropolitan Region of Chile in which we asked the adherence to these measures in August-September 2021 and retrospectively for 2020. With the answers obtained we fit a logistic regression model in which the response variable is the relaxation of each of the self-care preventive actions. The explanatory variables used are socio-demographic characteristics such as the age, sex, income, and vaccination status of the respondents. The results obtained show that there has been a significant decrease in adherence to the three personal protection measures in the Metropolitan Region of Chile. In addition, it was observed that younger people are more likely to relax these measures. The results show the importance of generating new incentives for maintaining adherence to personal protection measures. Copyright: © 2022 Varas et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.